2017
DOI: 10.1038/s41598-017-08780-7
|View full text |Cite
|
Sign up to set email alerts
|

Diethylstilbestrol administration inhibits theca cell androgen and granulosa cell estrogen production in immature rat ovary

Abstract: Diethylstilbestrol (DES), a strong estrogenic compound, is well-known to affect the reproductive system. In this study, we investigated the effects of DES administration on gonadotropin levels and ovarian steroidogenesis in prepubertal rats. DES treatment acutely reduced serum LH levels, followed by a reduction in the expression of various steroidogenesis-related genes in theca cells. Serum FSH levels were almost unaffected by DES-treatment, even though Cyp19a1 expression was markedly reduced. Serum progestero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 64 publications
1
11
0
Order By: Relevance
“…Moreover, after co-culture, the hierarchical GC gene expression of CCND1 ( Figure 6), ACC (Figure 4), and genes in the steroidogenesis pathway ( Figure 5) also showed the same trend (increased significantly at 48 h and decreased significantly at 96 h), while the gene expression of BCL2, PPARγ and FAS also showed a similar trend (but not significant at either time point) of promotion followed by inhibition. This confirmed that TCs had a complex and time-dependent effect on hierarchical GCs [18,49] and further supported that in hierarchical and F1 follicles, there might be some synergies and interactions between proliferation, anti-apoptosis, DNL and steroidogenesis pathways when TCs are affecting GCs [27,36,50,51]. However, interestingly, the effects of TCs on the functional pathways of F1 GCs and hierarchical GCs at 96 h were similar (Figures 4-6).…”
Section: Discussionsupporting
confidence: 72%
“…Moreover, after co-culture, the hierarchical GC gene expression of CCND1 ( Figure 6), ACC (Figure 4), and genes in the steroidogenesis pathway ( Figure 5) also showed the same trend (increased significantly at 48 h and decreased significantly at 96 h), while the gene expression of BCL2, PPARγ and FAS also showed a similar trend (but not significant at either time point) of promotion followed by inhibition. This confirmed that TCs had a complex and time-dependent effect on hierarchical GCs [18,49] and further supported that in hierarchical and F1 follicles, there might be some synergies and interactions between proliferation, anti-apoptosis, DNL and steroidogenesis pathways when TCs are affecting GCs [27,36,50,51]. However, interestingly, the effects of TCs on the functional pathways of F1 GCs and hierarchical GCs at 96 h were similar (Figures 4-6).…”
Section: Discussionsupporting
confidence: 72%
“…BPA lowers progesterone biosynthesis and reduces the mRNA levels of Hsd3b1 , Cyp11a1 and Cyp19a1 in human granulosa cells (Mansur et al, ; Mansur et al, ), whereas it increases progesterone accumulation and expression of StAR, Cyp11a1 and Hsd3b1 in immature rat granulosa cells (Samardzija et al, ). Exposure of immature rat ovaries to diethylstilbestrol causes alterations in the expression of a number of steroidogenic genes followed by a decrease in the progesterone, estradiol and testosterone production (Imamichi et al, ). Similarly, genistein inhibits growth and alters steroidogenesis in adult mouse antral follicles (Patel, Peretz, Pan, Helferich, & Flaws, ).…”
Section: Discussionmentioning
confidence: 99%
“…whereas it increases progesterone accumulation and expression of StAR, Cyp11a1 and Hsd3b1 in immature rat granulosa cells . Exposure of immature rat ovaries to diethylstilbestrol causes alterations in the expression of a number of steroidogenic genes followed by a decrease in the progesterone, estradiol and testosterone production (Imamichi et al, 2017 (Soma, Sinchak, Lakhter, Schlinger, & Micevych, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA from each tissue and the cultured cells was extracted using Tripure reagent (Roche). RT‐PCR and quantitative polymerase chain reaction (qPCR) were performed as described (Imamichi et al, ). In qPCR, the expression of ach gene was measured by RT‐PCR and then normalized using 36B4 expression.…”
Section: Methodsmentioning
confidence: 99%
“…COX-2: cyclooxygenase 2; CHOP: C/EBP homolog protein; GAPDH: glyceraldehyde 3-phosphate dehydrogenase; hCG: human chorionic gonadotropin; RT-PCR: real-time polymerase chain reaction; SEM: standard error of mean 4.4 | Real-time polymerase chain reaction and quantitative polymerase chain reaction Total RNA from each tissue and the cultured cells was extracted using Tripure reagent (Roche). RT-PCR and quantitative polymerase chain reaction (qPCR) were performed as described (Imamichi et al, 2017). In qPCR, the expression of ach gene was measured by RT-PCR and then normalized using 36B4 expression.…”
Section: Dna Microarray Analysismentioning
confidence: 99%